2020
DOI: 10.3390/fluids5040233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inflow Condition on RANS and LES Predictions of the Flow around a High-Rise Building

Abstract: An increasing number of engineering applications require accurate predictions of the flow around buildings to guarantee performance and safety. This paper investigates the effects of variations in the turbulent inflow, as predicted in different numerical simulations, on the flow pattern prediction around buildings, compared to wind tunnel tests. Turbulence characteristics were assessed at several locations around a model square high-rise building, namely, above the roof region, at the pedestrian level, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For LES validation and comparison with RANS models, Vita et al [122] simulated the flow pattens around high-rise buildings based on the turbulent inflow variations. It was found that RANS models are accurate only for some situations.…”
Section: Les Modelsmentioning
confidence: 99%
“…For LES validation and comparison with RANS models, Vita et al [122] simulated the flow pattens around high-rise buildings based on the turbulent inflow variations. It was found that RANS models are accurate only for some situations.…”
Section: Les Modelsmentioning
confidence: 99%
“…For the high-rise skyscrapers, the mean velocities, turbulent kinetic energies, tracer concentrations, and Reynolds stresses were recently studied using adaptive LES by Aristodemou et al 39 to discover how they affect the local environment. Using RANS and LES, Vita et al 40 investigated the wind velocity around a high-rise building and provided a detailed analysis of the pedestrian level, roof and wake regions. Recently, indoor airflow dynamics in a room with a partition have been investigated using the large eddy-simulation lattice Boltzmann method by Haque et al 41 Very recently, Hassan et al 42 have investigated the airflow dynamics around a square shape high-rise building using the unsteady realizable k - ε RANS approach for Re = 12000 .…”
Section: Introductionmentioning
confidence: 99%